In-vitro Screening of some Chemicals and Biocontrol Agents against Erwinia carotovora subsp. carotovora, the Causal Agent of Soft Rot of Potato (Solanum tuberosum) (The Agriculturists, 2013)
Erwinia carotovora subsp. carotovora was isolated from the infected potato tuber and was identified by pathological, morphological and biochemical studies. Five chemicals viz. Cupravit 50 WP (Copper oxychloride), Sulcox 50 WP (Copper oxychloride), Champion 77 WP (Copper hydroxide), Indofil M- 45 (Mancozeb) and Bavistin 50 WP (Carbendazim) and five biocontrol agents viz. Bacillus subtilis, Pseudomonas fluorescens, Rhizobium leguminosarum, Trichoderma harzianum and Aspergillus flavus were screened out in vitro against the growth of Erwinia carotovora subsp. carotovora by well diffusion method measuring the inhibition zone. Among the chemicals, Sulcox 50 WP (Copper oxychloride) was highly effective against it with 31.00 mm inhibition zone after 48 hours of incubation at 0.2% concentration when 100 ?l/well was used. In case of biocontrol agents, Bacillus subtilis was the best against the bacterium with 16.67 mm inhibition zone after 48 hours of incubation. DOI: http://dx.doi.org/10.3329/agric.v11i2.17480 The Agriculturists 2013; 11(2) 1-9